Vulvovaginal candidiasis in primary health care: screening of women diagnosed in municipalities in the central region of the State of Tocantins, Brazil (Research, Society and Development, 2022)
Vulvovaginal candidiasis consists of an infection of the vulva and vagina caused by fungi of the genus Candida, especially when there is an unbalance of the vaginal microbiota, resulting in signs such as redness, intense itching and vaginal discharge. By representing the diagnosis of aforementioned gynecological infection, the present study has as main objective to verify the prevalence of vulvovaginal candidiasis through the results of cytopathological exams carried out in the Basic Health Units - UBS of the municipalities of the central region of the State of Tocantins, Brazil. This is a cross-sectional, exploratory and descriptive research, with a qualitative and quantitative approach, covering examinations of women who received care at UBS in the municipalities of Colmeia and Pequizeiro. Through the analysis of the results, it can be observed that, among the 30 samples with vulvovaginal candidiasis, there was a prevalence of suggestiveness of bacterial vaginosis, with a representativeness of 80%, and the presence of Lactobacillus sp., being pointed out in 60% of the analyzed exams. There was also, in a lower percentage, the indication of suggestive of Gardnerella vaginalis, with a value of 16,7%. Leucorrhoea was diagnosed in 26,7% of the exams under study, while the observation of an inflammatory process could be detected in most patients, in 86,7% of the cases. Therefore, carrying out the present study made it possible to point out the significant occurrence of association of vulvovaginal candidiasis with other infections, being of paramount importance the orientation and adoption of the appropriate treatment by the patients.